Phase Contrast Spine MRI for the Evaluation of CSF Leak, and Why It Matters. (14th February 2023) - Carroll, Ian; Callen, Andrew
Abstract : For 2 decades, spine MRI was considered a reliable and sensitive modality for detecting CSF leaks based on (1) its ability to detect high rates of epidural collections among selected small cohorts of patients with spontaneous intracranial hypotension (SIH) 1 and (2) the observation that up to 91% of patients showing an epidural collection on traditional CT myelography also show epidural collections on spine MRI. 2 Based on these and other similar reports suggesting high sensitivity, spine MRI has been used as part of the standard first-line evaluation of patients with suspected CSF leaks.